Development and Testing of a Novel Arm Cranking-Powered Watercraft - Fuglsang, Thomas; Padulo, Johnny; Spoladore, Massimo; Dalla Piazza, Michele; Ardigò, Luca P. (Frontiers in Physiology, 2017)
There is a lack of human-powered watercrafts for people with lower-body disabilities. The purpose of this study was therefore to develop a watercraft for disabled people and investigate the metabolic cost and efficiency when pedaling. The watercraft was designed by combining parts of a waterbike and a handbike. Nine able-bodied subjects pedaled the watercraft at different speeds on a lake to provide steady-state metabolic measurements, and a deceleration test was performed to measure the hydrodynamic resistance of the watercraft. The results showed a linear correlation between metabolic power and mechanical power (r2=0.93). Metabolic expenditure when pedaling the watercraft was similar to other physical activities performed by people with lower-body disabilities. Moreover, the efficiency of the watercraft showed to be comparable to other human-powered watercraft and could, as a result, be an alternative fitness tool especially for people with lower-body disabilities, who seek water activities. A number of suggestions are proposed however, to improve the efficiency and ergonomics of the watercraft.